Miscibility, mechanical properties and degradation behaviour of polylactic acid/thermoplastic polyurethane blends compatibilized by Ema-Gma - Mudrikah Sofia binti Mahmud (Kulliyyah of Engineering, International Islamic University Malaysia, 2019)
Polylactic acid (PLA) is known as a green material which possesses excellent biodegradability and renewability with good mechanical performance in terms of tensile strength. However, PLA is naturally brittle and has low impact strength which restrict its application in some specific fields. One of the potential alternatives to encounter the brittleness of PLA is by blending it with thermoplastic polyurethane (TPU), since TPU has several attractive properties such as high toughness and flexibility. Yet, it is difficult to acquire miscible blend and this could be encountered with the use of compatibilizer. On the other hand, limited works have been reported on the effect of ethylene-methyl acrylate-glycidyl methacrylate (EMA-GMA) compatibilizer on properties of PLA/TPU blends. Thus, in this work, the effect of EMA-GMA in various blend compositions on miscibility, morphological development, mechanical properties, water absorption and degradation behaviors of PLA/TPU blends were analyzed. The blends were prepared through melt blending technique and analysis of miscibility and morphological development were conducted by using dynamic mechanical analysis (DMA), fourier-transform infrared spectroscopy (FT-IR) and scanning electron microscopy (SEM), while evaluation of mechanical properties were performed through tensile and impact tests. Degradation behavior was analyzed from soil burial test and hydrolytic degradation test. FT-IR analysis proved that EMA-GMA has been successfully compounded in PLA/TPU blends with disappearance of epoxy ring at transmittance band of ~910 cm-1 which indicated reactive compatibilization. DMA displayed the shifting between two detected Tg peaks towards each other, indicating the inclusion of EMA-GMA improved the miscibility of PLA/TPU blends. It is further proven with SEM observation, which inclusion of EMA-GMA promoted uniform distribution with smaller size of droplets throughout the matrix. Addition of EMA-GMA improved mechanical properties of PLA which is indicated by significant increment of elongation at break and impact strength of PLA/TPU blends with some composition exhibited non-break behavior. Water resistance of PLA/TPU blends were significantly improved with addition of EMA-GMA, which consistent with low degradation rate of compatibilized blends, in soil and hydrolytic degradation tests. Overall, addition of EMA-GMA in PLA/TPU blends improved the miscibility of the blends with some proof of reactive compatibilization that lead to improvement in mechanical properties and water resistance and reduce the degradation rate in soil and alkaline solution.